2022
DOI: 10.1101/2022.02.11.480130
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Substrate Binding and Inhibition of the Anion Exchanger 1 Transporter

Abstract: Anion Exchanger 1 (AE1, SLC4A1) is the primary bicarbonate (HCO3-) transporter expressed in erythrocyte membranes where it mediates transport of CO2 between lungs and other tissues via import/export of bicarbonate. It is also a key regulator of erythrocyte structure and antigenic recognition. Previous biochemical studies, and a low-resolution crystal structure of the transmembrane domain have provided initial insight into AE1 structure and function. However, key questions remain regarding substrate binding and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The residue R730 on TM10 of Band 3 is the most likely binding site, which agrees with the previous experiments. 6,25 Furthermore, we demonstrate that the binding stability of bicarbonate ions in Band 3 is determined by the combined interactions of several residues together with R730 imposed on the ions. CHOL in the lipid bilayer has a remarkable impact on the binding of the bicarbonate ions in Band 3, with an optimal CHOL concentration revealed for the bicarbonate ion binding.…”
Section: ■ Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…The residue R730 on TM10 of Band 3 is the most likely binding site, which agrees with the previous experiments. 6,25 Furthermore, we demonstrate that the binding stability of bicarbonate ions in Band 3 is determined by the combined interactions of several residues together with R730 imposed on the ions. CHOL in the lipid bilayer has a remarkable impact on the binding of the bicarbonate ions in Band 3, with an optimal CHOL concentration revealed for the bicarbonate ion binding.…”
Section: ■ Introductionmentioning
confidence: 73%
“…The results shown in Figure 3 agree well with the experiments which also indicated that R730 is one of the most probable binding sites for bicarbonate ions in the Band 3 cavity. 6,25 We speculate that K539 and E535 act as bridging residues in the binding process of the bicarbonate ion, driving the anions into the Band 3 cavity and facilitating their transfer to the final binding site of R730. In the next process of the anion transport occurring in the natural plasma membrane of erythrocyte, the bicarbonate ion will separate from R730 and transport across Band 3.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Might any of these residues interact with solute? There is no structure of a borate transporter bound to its solute, so we performed a superposition of a structure of bicarbonate-bound human SCL4A1 [ 42 ] with the AlphaFold ScBor1p model (RMSD = 3.149 Å) ( Figure 4 F) [ 29 ]. As suspected, the bicarbonate places in the cavity formed where TM3 and TM10 meet.…”
Section: Resultsmentioning
confidence: 99%
“…Among amino acids identified in this study, Q396 and Y212 are closest to where bicarbonate superposes. In human SLC4A1, R730 is homologous with Q396 and is observed to interact directly with bicarbonate [ 42 ]. Interestingly, the carboxylate group of D347 is located 8.2 Å away from the superposed bicarbonate carbon.…”
Section: Resultsmentioning
confidence: 99%